1991
DOI: 10.1159/000204796
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Granulocyte-Macrophage Colony-Stimulating Factor in Cerebrospinal Fluid of Patients with Aseptic Meningitis

Abstract: The level of granulocyte-macrophage colony-stimulating factor (GM-CSF) in the cerebrospinal fluid from 14 infants and children with meningitis and 6 patients who suffered other diseases besides meningitis was measured by our sensitive enzyme linked immunosorbent assay for GM-CSF. The minimal detection level of GM-CSF was 40 pg/ml. Six of 9 patients (67%) with aseptic meningitis had detectable GM-CSF in cerebrospinal fluid and the concentrations of GM-CSF ranged from 49 to 114 pg/ml (mean 72 pg/ml), whereas non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
15
2
Order By: Relevance
“…However, it is difficult at the initial stage to distinguish aseptic meningiti s from purulent meningitis by neutrophil counts alone. G-CSF in the cerebrospinal fluid increases in aseptic meningiti s. The peak levels reach 386 ng/L as shown in our study or 366 ng/L as reported by others (25). We also measured G-CSF levels in the cerebrospinal fluid in a case of pneumococcal purulent meningitis.…”
Section: Relationship Between G-csf Levels and Clinical Indicessupporting
confidence: 87%
See 1 more Smart Citation
“…However, it is difficult at the initial stage to distinguish aseptic meningiti s from purulent meningitis by neutrophil counts alone. G-CSF in the cerebrospinal fluid increases in aseptic meningiti s. The peak levels reach 386 ng/L as shown in our study or 366 ng/L as reported by others (25). We also measured G-CSF levels in the cerebrospinal fluid in a case of pneumococcal purulent meningitis.…”
Section: Relationship Between G-csf Levels and Clinical Indicessupporting
confidence: 87%
“…The G-CSF levels were 4700 ng/L on the third day of illness, 111 ng/L on the fifth day, and below sensitivity on the seventh day, when meningeal symptoms had disappeared. Shimoda et al (25) reported that G-CSF levels in the cerebrospinal fluid markedly increased and averaged 1500 ng/L in 10 of 11 cases of purulent meningitis. These levels-in both their investigation (25) and ours-in patients with purulent meningitis were significantly higher (p < 0.05) than those in our patient s with aseptic meningitis.…”
Section: Relationship Between G-csf Levels and Clinical Indicesmentioning
confidence: 99%
“…Unlike other cytokines such as TNF-␣ or IL-1 in another experiment [23], G-CSF injected i.c. did not cause migration of leucocytes into the subarachnoid space, although the concentrations which were presumably present in the CSF in this study (Ϸ 5 g/ml and 1 g/ml) assuming a CSF volume of 2 ml, were substantially higher than those observed in humans with bacterial meningitis (mean Ϸ 1500 pg/ml [6]). For this reason, G-CSF in CSF appears not to be directly involved in granulocyte recruitment or at least will not be the only substance being responsible for the recruitment of granulocytes.…”
Section: Discussioncontrasting
confidence: 65%
“…G-CSF, and after migration into the central nervous system, release larger amounts of TNF and IL-1␤ into the CSF than leucocytes not activated by G-CSF. In humans, in the CSF increased levels of G-CSF were observed both in bacterial [6,21] and viral [22] central nervous system infections. Unlike other cytokines such as TNF-␣ or IL-1 in another experiment [23], G-CSF injected i.c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation